Financial Literacy Guidance Services for Children of Migrant Workers in Bangserreh Village Pamekasan Madura - Anas, Achmad Tarmidzi (Civiliza Publishing, 2024)
The financial literacy mentorship program for children of migrant worker families in Bangserreh Village aims to improve the financial understanding and skills of children from migrant worker families. The program's main objective is to teach essential financial management, including budgeting, saving, and investment, and establish positive financial habits among participants. The approach used is Asset-Based Community-Driven Development (ABCD), which emphasizes the empowerment of local potential and community participation in the learning process. The program was implemented over four meetings with mentoring stages, including an introduction to financial literacy, budgeting, saving, investment, simulation practice, and group discussions. Evaluation results showed a significant increase in understanding, with 80% of participants able to categorize the use of their pocket money, 75% understanding the importance of saving, and 70% practicing more structured pocket money management. The socio-economic impact is also reflected in the increased involvement of migrant families in the local economy and family financial management. Before the program, only 40% of families had a monthly budget; this figure increased to 65% after program implementation. In addition, 70% of migrant families are now better able to save regularly and avoid consumptive debt. Overall, the program makes a significant contribution to improving the financial literacy of children of migrant families, which has a direct impact on the economic well-being of their families. With a better understanding of financial management, migrant families can be better integrated into the socio-economic life of the village and better able to manage irregular income. The program also opens up opportunities for long-term economic development in migrant communities.